2024
DOI: 10.1146/annurev-publhealth-040617-014101
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Determinants of Breast Cancer

Abstract: In the United States, breast cancer is the most common invasive malignancy and the second most common cause of death from cancer in women. Reproductive factors, estrogen, and progesterone have major causal roles, but concerns about other potential causes in the external environment continue to drive research inquiries and stimulate calls for action at the policy level. The environment is defined as anything that is not genetic and includes social, built, and chemical toxicant aspects. This review covers the sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 152 publications
(151 reference statements)
0
53
0
Order By: Relevance
“…The vast majority of breast cancers are diagnosed over the age of 50 and aging has been is associated with the accumulation of genetic, epigenetic, and hormonal alterations [25 , 26] . Several other factors have been associated with an increased occurrence of breast cancers including mammographic density [27] , reproductive factors (early age of menarche, late menopause, low parity, late age at first birth [28 , 29] ), anthropometric features (height [30] and body mass index for postmenopausal women [31] , hormone replacement therapy [32] , oral contraceptive pills [33] , exposure to diethylstilbestrol [34] , previous exposure to radiation therapy [35] , lifestyle factors (physical activity [36] , alcohol consumption [37] , night shift [38] ), and exposure to various chemicals [39] .…”
Section: Breast Cancer Risk Factorsmentioning
confidence: 99%
“…The vast majority of breast cancers are diagnosed over the age of 50 and aging has been is associated with the accumulation of genetic, epigenetic, and hormonal alterations [25 , 26] . Several other factors have been associated with an increased occurrence of breast cancers including mammographic density [27] , reproductive factors (early age of menarche, late menopause, low parity, late age at first birth [28 , 29] ), anthropometric features (height [30] and body mass index for postmenopausal women [31] , hormone replacement therapy [32] , oral contraceptive pills [33] , exposure to diethylstilbestrol [34] , previous exposure to radiation therapy [35] , lifestyle factors (physical activity [36] , alcohol consumption [37] , night shift [38] ), and exposure to various chemicals [39] .…”
Section: Breast Cancer Risk Factorsmentioning
confidence: 99%
“…Breast cancer (BC) is the leading cause of cancer-associated death (15%: 626,679 cases) and the most commonly diagnosed cancer (24%: 2,088,849 cases) among women worldwide 1 . BC is characterized by a complex interaction between environmental factors and biological aspects, such as gene deregulation, hormone disruption or ethnicity 24 . Despite subtype-specific treatment efforts, advanced BC with distant organ metastases is considered incurable 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have attempted to assess the association between the exposure to environmental chemicals and breast cancer or some relevant outcome of breast cancer (eg, obesity) . Accumulating evidence from experimental, clinical, and ecological research has suggested that environmental factors play an important role in one or more possible pathways in the etiology of breast cancer; therefore, it is necessary to pay attention to the environmental causes of breast cancer.…”
Section: Introductionmentioning
confidence: 99%